Contributions of remote collaborative sketching to the design of infovis in public health - Velloso, Leandro Manuel Reis; Fontes de Carvalho, Mailson; Momberg Araújo, Gabriela; Marcus Jarske, Johne; Anísio Garcia, Luciano; Sérgio de Souza, Luiz; Ito, Marcia; Nice Alves-Souza, Solange; Letícia dos Santos, Tânia; Mathias Fernandes, Henrique; et al. (InfoDesign, 2023)
This paper presents contributions from using remote collaborative sketching to infovis for public health. The results come from an interdisciplinary study that involved designers, health researchers, public managers and computer scientists in the production of sketches generating alternatives for creating valuable graphics and dashboards. One of the creative stages was the remote collaborative workshops in which design alternatives were proposed based on sketches. The sketches were developed with the support of videoconferencing meetings, virtual boards, and graphic tablets. From this practice, we were able to include as contributions to the creative process in infovis: remote collaboration expansion; agile and iterative cycles improvement; interface design preview; data modeling supporting; addressing graphic literacy issues; creative process documentation; participant experience improvement; and additional information incorporation.